Distribution of bottom vegetation of the shallow water zone in Karkinitskiy Bay of the Crimean Peninsula - T. V. Pankeeva; N. V. Mironova; Yu. N. Goryachkin; L. V. Kharitonova (Юг России: экология, развитие)
Aim. To identify the distribution features of a key species of macrophytobenthos in the shallow water zone of Karkinitskiy Bay.Material and Methods. The field materials from a comprehensive expedition carried out during the summer 2019 were collected and processed by the authors.Results. For the first time, a map was compiled and the features of the distribution of dominant types of macrophytobentos identified in the shallow water zone of Karkinitskiy Bay.Conclusion. It was shown that in the eastern part of the bay, on a shallow slope composed of silty‐sandy deposits, adjacent to the accumulative shores, sea grasses dominate and along the abrasive‐clay shores there is no bottom vegetation and significant accumulations of dead leaves of Zostera marina и Z. noltei are typical there. In the water area of the Bakal spit macrophitobentos is not found on the sandy deposits. Cladophora spp. are represented in the base of the western branch of the spit, at the place of its joining an active clayey cliff. Mosaic distribution of bottom vegetation is noted in the area of Cape Kamenniy, where co‐growth of algae on the limestone outcrops and marine herbs living on loose soils is registered. West of Cape Kamenniy in shallow water adjacent to the abrasive limestone coasts Carpodesmia crinite – Treptacantha barbata phytocenoses are characteristic. It was shown that in the composition of macrophytobentos decreased in the role of dominant species, an increase in the proportion of algae found in the areas with increased eutrophication of marine environment, which is probably due to the influence of anthropogenic and natural factors. Monitoring observations in this area will make it possible to develop scientifically based recommendations aimed at optimizing the environmental regime and rational environmental management of the coastal zone of Karkinitskiy Bay.